Aplikasi Tutorial Pembelajaran Anatomi Tubuh Manusia Menggunakan Manusia - Rastari, Unsta Nastiti Lingga; , Hernawan Sulistyanto, S.T., M.T (2017)
For long time, list reference for learning human anatomy only in textbook, papers, and textbook clinic. It is less because does not get a visual demonstration from topic of anatomy. Learning anatomy needed recurring visual experience. Therefore researcher made learning anatomy tutorial application using the website. The website contains a summary of important anatomical simple and accompanied by a detailed knowledge of the structure of the human body illustration. The website adapted to draft plans learning to their students ninth grade junior high school. Methods the website is the waterfall which will then tested to their students ninth grade junior high school. Using this website can helplerning human anatomy more effective and fun. Implementation of this application may increase the attractiveness of the students toward science subjects are anatomy of the human body, especially the reproductive system.